Fragmented lives, assembled parts : culture, capitalism, and conquest at the U.S.-Mexico border - Lugo, Alejandro, 1962- (University of Texas Press, 2008)
Established in 1659 as Misión de Nuestra Señora de Guadalupe de los Mansos del Paso del Norte, Ciudad Juárez is the oldest colonial settlement on the U.S.-Mexico border-and one of the largest industrialized border cities in the world. Since the days of its founding, Juárez has been marked by different forms of conquest and the quest for wealth as an elaborate matrix of gender, class, and ethnic hierarchies struggled for dominance. Juxtaposing the early Spanish invasions of the region with the arrival of late-twentieth-century industrial "conquistadors," Fragmented Lives, Assembled Parts documents the consequences of imperial history through ethnographic studies of working-class factory life. By comparing the social and human consequences of recent globalism with the region's pioneer era, Alejandro Lugo demonstrates the ways in which class mobilization is itself constantly being "unmade" at both the international and personal levels for border workers. Both an inside account of maquiladora practices and a social history, this is an interdisciplinary survey of the legacies, tropes, economic systems, and gender-based inequalities reflected in a unique cultural landscape. Through a framework of theoretical conceptualizations applied to a range of facets--from multiracial "mestizo" populations to the notions of border "crossings" and "inspections," as well as the recent brutal killings of working-class women in Ciudad Juárez--Fragmented Lives, Assembled Parts provides an understanding of the effect of transnational corporations on contemporary Mexico, calling for official recognition of the desperate need for improved working and living conditions within this community. --From publisher's description